1984
DOI: 10.1002/em.2860060503
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous mutation frequencies in Salmonella: Enhancement of G/C to A/T transitions and depression of deletion and frameshift mutation frequencies afforded by anoxic incubation

Abstract: Incubation of Salmonella typhimurium under anoxic conditions (0.1% oxygen or less) results in a substantial decrease in small (3-and 6-basepair) deletions in an A/T-rich region of the hisG gene in the hisG428 ochre mutant and also decreases the frequency of minus frameshift mutations in G/C-rich sequences in the his-D3052 and hisC3076 mutants. In contrast, the frequency of G/C-----A/T transition mutations increases substantially during anoxic growth of hisG46. Growth of revertants of strains carrying accessory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

1984
1984
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 66 publications
(17 reference statements)
0
11
1
Order By: Relevance
“…The frequency of deletions in the lacI gene of E. coli is reduced to 1/25th in a recA mutant (3). Anaerobic growth also results in a preferential reduction in the frequency of deletion revertants of hisG428 (to approximately 1/3), and the frequency is further reduced (to approximately 1/10) in the recA derivative under these conditions (32). This result suggests that at least two independent pathways exist for the generation of the small deletions monitored in this system.…”
Section: Discussionmentioning
confidence: 95%
“…The frequency of deletions in the lacI gene of E. coli is reduced to 1/25th in a recA mutant (3). Anaerobic growth also results in a preferential reduction in the frequency of deletion revertants of hisG428 (to approximately 1/3), and the frequency is further reduced (to approximately 1/10) in the recA derivative under these conditions (32). This result suggests that at least two independent pathways exist for the generation of the small deletions monitored in this system.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that oxygen metabolism influences DNA damage in mammals (6, 7) and bacteria. Hartman et al (8) showed that Salmonella typhimurium strains grown under aerobic conditions had increased frequencies of small deletion and frameshift mutations relative to strains grown anaerobically, while the frequency of G-C to AT transitions was depressed under the aerobic conditions. Recently, Farr et al (9) showed that Escherichia coli mutants that lack both the manganese-and iron-containing superoxide dismutases (sodA sodB double mutants) have enhanced spontaneousmutation frequencies compared to wild-type strains during aerobic growth.…”
mentioning
confidence: 99%
“…Sequence analysis of hisG46 revertants has demonstrated that any of five single transitions/transversions (TCC, ACC, GCC, CAC, and CTC) at the first two positions of the hisG46 revertant codon 69 (CCC) can give rise to His ϩ prototrophs [Barnes et al, 1982;Hartman et al, 1984]. Reversions of hisG46 can also occur via extragenic suppression resulting from a T/A 3 G/C transversion within the anticodon of either of two tRNA Thr genes .…”
Section: Molecular Analysis Of Salmonella Revertantsmentioning
confidence: 98%
“…The purified revertants of the hisG46 allele (TA100) were analyzed using the colony hybridization procedure developed by Cebula and Koch [1990] with modifications of Shelton et al [1994] in which six 32 P-labeled probes (5'-GTCGATTCCGGTATT-3', 5'-GTCGATACCGGTATT-3', 5'-GTCGATGCCGGTATT-3', 5'-GTC-GATCACGGTATT-3', 5'-GTCGATCTCGGTATT-3', 5'-GTCGATC-CCGGTATT-3') were used. Six revertant strains containing the six classes of mutations, confirmed by PCR/DNA sequence analysis according to previous sequence information [Hartman et al, 1984], were used as positive controls for the six probes. Two independent hybridizations were performed with each probe in order to confirm the revertant genotype.…”
Section: Molecular Analysis Of Salmonella Revertantsmentioning
confidence: 99%